Response of Growth Indices in Black Gram due to Rhizobium Inoculation - Nitu, SK; Haider, SA (Journal of Life and Earth Science, 2011)
Key words: Growth indices; black gram; Rhizobium. DOI: 10.3329/jles.v3i0.7447 J. Life Earth Sci., Vols. 3-4: 51-54, 2009